Job insecurity, psychological safety, work alienation, and anxiety in the hotel industry: a moderated-mediated analyses - Hassane Gharbi; Abu Elnasr E. Sobaih; Nadir Aliane (Frontiers in Psychology)
IntroductionWhen hotels no longer keep their promises to their employees, particularly in terms of job security, employees may feel less motivated to perform their tasks. With the certainty of being wronged, they risk falling prey to the hegemony of workplace alienation and anxiety.MethodsFor this purpose, a quantitative methodology, particularly structural equation modeling, was employed to analyse responses from 516 employees working in hotels in Tunisia.Results and discussionThe findings confirmed that job insecurity had a significant and positive influence on anxiety and alienation at work. In addition, alienation at work significantly and positively influenced the anxiety experienced by employees. The results showed that the relationship between job insecurity and anxiety remained significant after the introduction of work alienation as a mediating variable. The mediation effect of work alienation was confirmed to be partial in the relationship between job insecurity and work-related anxiety. The moderator effect analysis revealed that psychological safety significantly reduced the negative impact of job insecurity on employees' anxiety levels. The research provides useful suggestions to help managers and decision-makers mitigate feelings of alienation at work and high levels of anxiety among employees.